Criminal Liability of Offenders in Village Fund Corruption Cases under the Indonesian Anti-Corruption Law - Ogi Prasetia; Siti Marwiyah; Bahrul Amiq (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2026)
Purpose: This study examines the criminal accountability of Village Fund corruption perpetrators under Indonesia's AntiCorruption Law, with focus on the legal elements of authority misuse, state financial loss, and criminal intent (mens rea) within the governance framework of Law Number 6 of 2014 on Villages.Research Methodology: A qualitative normative juridical design was employed, supplemented by an empirical review of 15 court verdicts on Village Fund corruption issued between 2019 and 2024. Data were collected through library research and systematic analysis of statutory instruments, court rulings, and peer-reviewed publications.Results: Criminal accountability predominantly arises from village heads' misuse of their position as custodians of village finances, with most prosecutions grounded in Article 3 of the Anti-Corruption Law. Establishing state financial loss and demonstrating criminal intent were the decisive factors in securing conviction. Structural deficiencies in internal oversight and insufficient administrative competence at the village level were identified as key drivers of corruption vulnerability. Limitations: This study is limited to 15 purposively selected court decisions and does not address the liability of third parties such as vendors or contractors. Access to complete investigative audit records was also restricted, as such documents frequently remain confidential during the investigative phase.Conclusions: Criminal enforcement under the Anti-Corruption Law must be accompanied by governance reform and clearer normative boundaries between administrative errors and criminal conduct to uphold legal certainty and justice.Contributions: This research contributes to criminal law scholarship and provides practical recommendations for improving Village Fund governance and law enforcement consistency.